2019
DOI: 10.1007/s10266-019-00463-1
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and wear behavior of occlusal splint materials made of contemporary and high-performance polymers

Abstract: With the development of a digital technology of computer-assisted manufacturing (CAD/CAM) and new age materials, the use of new types of occlusal splint is to consider. The aim of the present study was to evaluate the surface roughness (Ra) and wear behavior of different CAD/CAM materials against enamel antagonist through a simulated chewing test. A total of 75 specimens made from ethylene vinyl acetate (EVA), polymethyl methacrylate (PMMA), polycarbonate (PC), polyetheretherketone (PEEK), and polyethylenetere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 47 publications
1
66
1
6
Order By: Relevance
“…The use of PEEK was additionally recommended for CAD-CAM fabricated occlusal splints. An in vitro study of Benli et al found lower loss of volume and change in roughness for PEEK occlusal splints after chewing simulation compared to other CAD-CAM materials such as vinyl acetate (EVA), polymethyl methacrylate (PMMA), polycarbonate (PC), and polyethyleneterephthalate (PETG) [ 11 ]. It was also claimed that milled PEEK intra-radicular posts could be an alternative to glass-fiber and cast-metal posts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PEEK was additionally recommended for CAD-CAM fabricated occlusal splints. An in vitro study of Benli et al found lower loss of volume and change in roughness for PEEK occlusal splints after chewing simulation compared to other CAD-CAM materials such as vinyl acetate (EVA), polymethyl methacrylate (PMMA), polycarbonate (PC), and polyethyleneterephthalate (PETG) [ 11 ]. It was also claimed that milled PEEK intra-radicular posts could be an alternative to glass-fiber and cast-metal posts.…”
Section: Resultsmentioning
confidence: 99%
“…Polyetheretherketone (PEEK) is a linear, aromatic, semi-crystalline thermoplastic, high performance polymer recently used in dentistry as a framework material for metal-free fixed dental prostheses [ 1 , 2 ], removable dental prostheses [ 3 ], implant-supported fixed prostheses [ 4 ], implant-retained overdentures [ 5 ], endocrowns [ 6 ] and resin bonded fixed dental prostheses [ 7 ]. It has been also used for the manufacturing of dental implants [ 8 ], implant abutments [ 9 ], healing abutments [ 10 ] and occlusal splints [ 11 ]. PEEK is a material with high biocompatibility, good mechanical properties, high temperature resistance, chemical stability, polishability, good wear resistance, low plaque affinity and high bond strength with veneering composites and luting cements.…”
Section: Introductionmentioning
confidence: 99%
“…This result agrees with previous studies, in which concentrations of saline-treated alumina 0.1% [41] and silver nanoparticles 0.2-8% [43] considerably improved the resin wear resistance of PMMA. In terms of the effect of surface roughness on wear resistance, Benli et al [44] investigated the relationship between the wear rate and surface roughness of occlusal splint materials made of contemporary and high-performance polymers and found that it is directly proportional. Furthermore, Nayyer et al [45] reported that surface roughness is affected by clinical adjustments such as polishing, because polishing leads to smooth surfaces that undergo less wear and provides the advantage of extended longevity of the restoration [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The surface roughness values of the study groups may also be explained by the effect of specimen preparation (milling) or polishing procedures. Additionally, clinical adjustments such as polishing affect the surface roughness of the material [42]. Therefore, polishing is recommended to obtain optimal clinical performance of dental polymers and to extend the longevity of the restoration.…”
Section: Hardness Testmentioning
confidence: 99%